Penguatan Program Makan Bergizi Gratis: Bukti Tingkat Sekolah tentang Literasi Nutrisi sebagai Mekanisme yang Sedang Berkembang - Ikwan Wahyudi; Linda Kharisma Cahyawati (Jurnal Bina Praja, 2026)
The Free Nutritious Meal Program (MBG) is a policy intervention aimed at meeting nutritional needs, including those of schoolchildren. However, its implementation practices at the school suggest a pedagogical dimension that could strengthen the program’s objectives by fostering consumption habits and awareness. This study aims to analyze how nutrition literacy functions as a reinforcing mechanism of MBG at the primary school level. The research employs a qualitative approach with a case study design in a public primary school in East Java, using semi-structured interviews with six teachers and 27 students, observations of MBG practices, and document analysis. Data analysis employed thematic analysis to identify patterns of practice, socio-pedagogical relations, and mechanisms emerging from everyday interactions. The results showed that nutrition literacy has developed implicitly through shared eating experiences, teacher-student interactions, and the habituation of consumption, yet remains excluded from the formal curriculum. The strengthening of MBG does not occur solely through policy design, but also through relational dynamics among teachers, students, and food consumption experiences that shape school-level mechanisms. These findings affirm that schools function as nodes for translating the policy into students’ concrete learning experiences, thereby positioning nutrition literacy as an emergent mechanism and practical medium for reinforcing the MBG program rather than merely a knowledge output. This study provides empirical contributions regarding the importance of a school practice-based approach in formulating strategies to strengthen MBG.